Tras las huellas de Pablo Neruda : Un homenaje a Hernán Loyola - Dawes, Greg (Editorial A Contracorriente, 2020)
"With these essays by the most appointed critics of the work of Pablo Neruda gathered here, this book aims to pay tribute to the great critic of the work of the Chilean Nobel Prize, Hernán Loyola. Some of them are dedicated to underlining their capital importance as a teacher in Chile or their enormous contribution to Nerudian studies while highlighting the personal side: their acute intelligence, their generosity, their humor, their eye for detail, their warmth human, its heterodoxy in terms of academics, among other things. The other unpublished essays address such topics as the dialectic of the earth and the sky, love and death, the correspondence between Darío Puccini and Neruda, the fantastic narratives of the poet, the intersection of narratives about the same impostor written by Baroja, Borges and Neruda, and his notion of democracy in its anarchist and avant-garde stage"--